p16INK4a immunocytochemistry versus human papillomavirus testing for triage of women with minor cytologic abnormalities: a systematic review and meta-analysis - Roelens, Jolien; Reuschenbach, Miriam; Knebel Doeberitz, Magnus von (Cancer cytopathology, 2012)
The best method for identifying women who have minor cervical lesions that require diagnostic workup remains unclear. The authors of this report performed a meta-analysis to assess the accuracy of cyclin-dependent kinase inhibitor 2A (p16INK4a) immunocytochemistry compared with high-risk human papillomavirus DNA testing with Hybrid Capture 2 (HC2) to detect grade 2 or greater cervical intraepithelial neoplasia (CIN2+) and CIN3+ among women who had cervical cytology indicating atypical squamous cells of undetermined significance (ASC-US) or low-grade cervical lesions (LSIL). A literature search was performed in 3 electronic databases to identify studies that were eligible for this meta-analysis. Seventeen studies were included in the meta-analysis. The pooled sensitivity of p16INK4a to detect CIN2+ was 83.2% (95% confidence interval [CI], 76.8%-88.2%) and 83.8% (95% CI, 73.5%-90.6%) in ASC-US and LSIL cervical cytology, respectively, and the pooled specificities were 71% (95% CI, 65%-76.4%) and 65.7% (95% CI, 54.2%-75.6%), respectively. Eight studies provided both HC2 and p16INK4a triage data. p16INK4a and HC2 had similar sensitivity, and p16INK4a has significantly higher specificity in the triage of women with ASC-US (relative sensitivity, 0.95 [95% CI, 0.89-1.01]; relative specificity, 1.82 [95% CI, 1.57-2.12]). In the triage of LSIL, p16INK4a had significantly lower sensitivity but higher specificity compared with HC2 (relative sensitivity, 0.87 [95% CI, 0.81-0.94]; relative specificity, 2.74 [95% CI, 1.99-3.76]). The published literature indicated the improved accuracy of p16INK4a compared with HC2 testing in the triage of women with ASC-US. In LSIL triage, p16INK4a was more specific but less sensitive. Cancer (Cancer Cytopathol) 2012. © 2012 American Cancer Society.